2023
DOI: 10.1186/s40634-023-00601-3
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in graft choice for primary anterior cruciate ligament reconstruction – part II: In‐vivo kinematics, patient reported outcomes, re‐rupture rates, strength recovery, return to sports and complications

Abstract: Postoperative patient satisfaction after anterior cruciate ligament reconstruction (ACL-R) is influenced mainly by the degree of pain, the need for reoperation, and functional performance in daily activities and sports. Graft choice has shown to have an influence on postoperative outcomes after ACL-R. While patient reported outcomes measurements do not differ between graft options, evidence shows that normal knee kinematics is not fully restored after ACL-R with an increase in postoperative anterior tibial tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 187 publications
0
24
0
Order By: Relevance
“…The addition of an allograft, while it increases overall graft diameter, may have detrimental efects as studies have shown that processed grafts could negatively impact biomechanical properties and patient outcomes [4,23,24]. The association between processing techniques for allografts used in HY grafts and outcomes following primary ACLR was outside the scope of the present study comparing < 8 mm HA to ≥ 8 mm HY.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of an allograft, while it increases overall graft diameter, may have detrimental efects as studies have shown that processed grafts could negatively impact biomechanical properties and patient outcomes [4,23,24]. The association between processing techniques for allografts used in HY grafts and outcomes following primary ACLR was outside the scope of the present study comparing < 8 mm HA to ≥ 8 mm HY.…”
Section: Discussionmentioning
confidence: 99%
“…2 Other options include allografts, tensor fascia Lata grafts, and artificial bands or augmentations, but these are usually reserved for rare cases or in the event of multiligament reconstructions requiring multiple transplants. 2,8,9 The BPTB historically has been considered the gold standard and has been the most commonly used graft for many years. 10 However, it has been gradually overtaken by the use of hamstrings that have become the most popular choice for primary ACL reconstruction both in the United States and in Europe.…”
Section: Video Transcriptmentioning
confidence: 99%
“…The QT is a stiff and robust graft, it has shown comparable biomechanical properties to quadrupled hamstrings and BPTB, with ultimate failure loads comparable to those of the native ACL. 8,9 The QT offers the possibility of harvesting a graft with bone block. Bone-to-bone healing has shown to be faster and more physiologic than tendon-to-bone interface.…”
Section: Video Transcriptmentioning
confidence: 99%
See 2 more Smart Citations